(untitled) - Garcia-Molina, Hector (Upper Saddle River, N.J., 2009)
This introduction to database systems offers a comprehensive approach, focusing on database design, database use, and implementation of database applications and database management systems.
Cơ sở dữ liệu
Keywords: Databases,Database management,Database design,Cơ sở dữ liệu,Quản trị cơ sở dữ liệu,Thiết kế cơ sở dữ liệu